2006
DOI: 10.1017/s0144686x06004818
|View full text |Cite
|
Sign up to set email alerts
|

The participation of older Europeans in volunteer work

Abstract: Today's discussion about the growing 'burden of ageing' must not neglect the substantial productive potential of the elderly population. Using micro-data from the new 'Survey of Health, Ageing and Retirement in Europe' (SHARE), we explore crossnational patterns of volunteering and the relationship between selected sociodemographic characteristics and participation in voluntary work among the population aged 50 and older in 10 countries. Our analysis reveals a clear spatial pattern of volunteering (with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
136
3
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 27 publications
13
136
3
8
Order By: Relevance
“…Whilst economists consider economic status as an effect of human capital (Becker 1964), according to Wilson and Musick's theory it should be treated as human capital because it qualifies individuals for voluntary work. The literature generally underlines, in agreement with resource theory, that older people with more human capital tend to volunteer more than those with less (Cutler and Hendricks 2000;Erlinghagen and Hank 2006).…”
Section: Individual Capital and Volunteeringsupporting
confidence: 54%
See 2 more Smart Citations
“…Whilst economists consider economic status as an effect of human capital (Becker 1964), according to Wilson and Musick's theory it should be treated as human capital because it qualifies individuals for voluntary work. The literature generally underlines, in agreement with resource theory, that older people with more human capital tend to volunteer more than those with less (Cutler and Hendricks 2000;Erlinghagen and Hank 2006).…”
Section: Individual Capital and Volunteeringsupporting
confidence: 54%
“…Acknowledging poor health as a barrier to volunteering, authors report a significant relationship between health and volunteering, with volunteering being explained by better health. This positive association emerged when health was self-rated (Choi 2003;Erlinghagen and Hank 2006;Erlinghagen 2010;McNamara and Gonzales 2011), measured in terms of functional limitations (Choi 2003;Hank and Stuck 2008;Suanet et al 2009), or in terms of mental health (Butrica et al 2009;Ahn et al 2011;Thomas 2011). The relationship between volunteering in older age and the number of chronic diseases was less evident in terms of its statistical significance (Erlinghagen and Hank 2006;Okun and Michel 2006;Ahn et al 2011).…”
Section: Health and Volunteeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the volunteer rate has been shown to be lower among older people, older volunteers offer more time than younger volunteers (Statistics Canada, 2009). Even if current trends in socioeconomic (Erlinghen & Hank, 2006) and health disparities (Boneham & Sixsmith, 2006) have a major impact on opportunities for social participation, older adults' plans for retirement are more diverse than ever (Lesemann, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has recurrently shown that, in general, retirement positively influences volunteering (Chambré, 1984;Choi, 2003;Erlinghagen & Hank, 2006;Hank & Erlinghagen, 2009;Mutchler, Burr, & Caro, 2003;Principi, Warburton, Schippers, & Di Rosa, 2012;van den Bogaard, Henkens, & Kalmijn, 2014), there are good reasons to suspect that this effect differs for people from various backgrounds. In social stratification research, the question whether is it mostly human capital or rather class that is at work as a differentiating factor in society has been debated extensively.…”
Section: Introductionmentioning
confidence: 93%